Manajemen Sekolah Dalam Meningkatkan Mutu Pendidikan Pada Tingkat SD - Ernawatie; Yossita Wisman; Akhmad Syarif (FKIP Universitas Palangka Raya, 2023)
The school management can mean everything pertaining to the management of the educational process to achieve the stated goals, both short-term goals, medium, or panjang. Tujuan term goal of this research was to determine the school management to improve the quality of education, to include: (1) Planning school programs; (2) The implementation of school programs and (3) Barriers faced. This study used a qualitative approach with descriptive methods, techniques of data collection is done through interview, observation guidelines, and documentation. Subjects were principals, supervisors and teachers in primary schools Boarding School-2 Middle Katingan district. Research results found: (1) planning school programs include: teaching programs, including: the need of teachers sharing teaching duties, procurement of textbooks, teaching tools and props, procurement or development of school laboratories, procurement or development of school libraries, system of assessment of learning outcomes, and curricular activities; (2) The implementation of school programs that the strategy adopted to achieve the improvement of the quality of education, include: socialization program, SWOT analysis, problem solving, quality improvement, and monitoring and evaluating the implementation of school programs; and (3) Barriers in planning school programs, among others, lack of community participation and economic difficulties so that their support for the management of low participating schools. It is expected that supervisors in order to direct and supervise principals in improving the quality of education on school program planning, program implementation and obstacles faced by appropriate, effective and efficient so that the quality of education in the schools can be improved.